Parameter analysis of vibratory energy flow in a hermetic compressor by statistical energy analysis - Barbosa, W. A.; Lenzi, A.; Zaninin, P.H. T. (Archives of Acoustics, 2003)
This work deals with the problem of vibratory energy flow from the internal electrical motor-compressor assembly (kit) to the shell of a hermetic compressor. The theoretical model is based on Statistical Energy Analysis. Shell and body vibratory energies have been measured at a standard operation condition, and the coupling loss factor thus obtained agreed well with predicted values calculated from impedance data. Several parameters, such as body and shell impedance, spring and shell loss factor, and model of the spring (tension and compression) were varied and their effects upon the compressor noise analyzed. Good agreement between theoretical and experimental results was observed.